Effects Of Organizational Commitment And Organizational Justice On Organizational Citizenship Behavior With Job Satisfaction As A Mediation - Sunaris, Deby; Wahyoedi, Soegeng; Tecoalu, Melitina (International Journal of Science, Technology & Management, 2022)
This study aims to determine the effect of organizational commitment, organizational justice and job satisfaction as a mediation on teacher OCB. The research subjects were 64 teachers who teach at the Gamaliel Christian School in Palu with an age range of 20-55 years. Data obtained through questionnaires distributed using google form. The analysis technique used is SEM-PLS (Structural Equation Model-Partial Least Square) using SmartPLS software version 3.3.2. The analysis results obtained that organizational justice has a positive effect on OCB, organizational commitment has a positive effect on OCB and organizational justice has a positive effect on OCB. While job satisfaction does not have a positive effect on OCB, organizational commitment does not have a positive effect on job satisfaction, organizational justice does not have a positive effect on OCB mediated by job satisfaction and organizational commitment has no positive effect on OCB mediated by job satisfaction. job satisfaction and OCB to teachers, the coefficient of determination of job satisfaction is only 17.9% which can be explained in this study, as well as the coefficient of determination of OCB is only 31.2% which can be explained in research i This means that there are about 82.1% of job satisfaction variables and 68.8% of OCB variables which can be explained from other variables outside the study such as motivation, transformational leadership. This study found that job satisfaction does not positively mediate organizational justice and organizational commitment to teachers, and this becomes input for the management of school organizational management.